Can improvements in our physiological understanding yield information on the utility of endothelial progenitor cell capture stents? - Kang, Hyun-Jae (The Korean journal of internal medicine, 2015)
As the authors thereof indeed discussed, the study wasobservational in nature and had associated limitations. However, the efforts of the cited work to elucidate thebiological differences between DES and EPC capturestents, using modern means of physiological evaluation,were valuable; the topic deserves further attention. KCI Citation Count: 0